2009
DOI: 10.15517/am.v21i1.4910
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de tres leguminosas como coberturas asociadas con maíz en el trópico subhúmedo

Abstract: La información de este trabajo formó parte de la tesis de Doctorado del primer autor, así como de la tesis de maestría en ciencias, del penúltimo y de la tesis de Licenciatura en Biología del último autor. 2 campus de ciencias Biológicas y agropecuarias-Universidad autónoma de Yucatán. Proyecto: "evaluación de leguminosas para intensificar la milpa en Yucatán" clave: 980603.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
(3 reference statements)
0
6
0
2
Order By: Relevance
“…The biomass produced by all the evaluated leguminous species was greater than 2 t ha -1 , being sufficient to fulfill the function of a cover crop by providing organic material to the soil (Castillo-Caamal et al 2010). The leaf biomass produced by centrosema in sacha inchi crops was statistically higher (8.6 t ha -1 ), if compared to the other treatments; however, bean produced the lowest leaf biomass (3.1 t ha -1 ) (Table 2).…”
Section: Speciesmentioning
confidence: 89%
See 1 more Smart Citation
“…The biomass produced by all the evaluated leguminous species was greater than 2 t ha -1 , being sufficient to fulfill the function of a cover crop by providing organic material to the soil (Castillo-Caamal et al 2010). The leaf biomass produced by centrosema in sacha inchi crops was statistically higher (8.6 t ha -1 ), if compared to the other treatments; however, bean produced the lowest leaf biomass (3.1 t ha -1 ) (Table 2).…”
Section: Speciesmentioning
confidence: 89%
“…The use of cover crops, in rotation or associated with crops of economic interest, is an important strategy to improve the soil and environment quality, soil fertility, organic matter accumulation, nitrates leaching mitigation, soil erosion processes reduction and weeds control, as well as the soil biological and physicochemical properties (Arévalo et al 1998, Bayer et al 2003, Castillo-Caamal et al 2010. These benefits will only be efficiently achieved if the selected cover crop species are adapted to the local environmental conditions and are appropriate for the defined agro-ecological target (Bodner et al 2010).…”
Section: Palavras-chavementioning
confidence: 99%
“…In a three-year evaluation in Yucatan of maize intercropped with mucuna or ib, there was no yield increase over that of monoculture maize (Castillo-Caamal et al, 2010). Castillo-Caamal and Caamal-Maldonado (2011) found that interspersing maize with mucuna at planting or 20 days after planting lowered maize yields, compared to monoculture or interspersing 40 or 60 days after planting.…”
Section: Fertility Managementmentioning
confidence: 99%
“…Seeds of six cultivars of M. pruriens were kindly gifted by Prof. Castillo Caamal [39]. Of these, M. pruriens var.…”
Section: Seed Material Their Production and L-dopa Extract Preparationmentioning
confidence: 99%